PENGARUH REALISASI ANGGARAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP KINERJA KEUANGAN, STABILITAS KEUANGAN, DAN INKLUSI KEUANGAN PADA PERUSAHAAN PERBANKAN DI BURSA EFEK INDONESIA TAHUN 2017 – 2022 - Isymam, Muhammad; Prasetyo, Andrian Budi (Diponegoro Journal of Accounting, 2024)
This research aims to determine the impact of corporate social responsibility budget realization on financial performance, financial stability, and financial inclusion in banking companies. The control variables used in this study are leverage, tangibility, firm size, and firm age. The population in this research consists of all banking companies listed on the Indonesia Stock Exchange for the period 2017-2022. The sample was selected using purposive sampling method, with a total of 22 banks included in the study. Hypothesis testing was conducted using multiple regression analysis on panel data.The results of this research indicate that the realization of corporate social responsibility budget has a positive influence on financial performance, financial stability, and financial inclusion. Tangibility and firm age do not have a significant impact on financial performance, financial stability, and financial inclusion. Leverage does not have a significant impact on financial performance and financial inclusion but has a positive impact on financial stability. However, firm size has a positive impact on financial performance, financial stability, and financial inclusion.